«Basta che non mi sposti le cose» L’ossessione: alcune note sulla diagnosi - Roccioletti, Gioia; Fabi, Marzia (Il sogno della farfalla, 2005)
The article reconstructs the history of psychiatric research into obsessive thinking and, also on the basis of an examination of some clinical cases, proposes a psychodynamic hypothesis based on the theory of birth by Massimo Fagioli. Obsessions offers us a problem of diagnosis: we find ourselves in front of a wide range of situations that go from normal thinking to an obsessive neurosis and end up in delirium, in psychosis. To diagnose correctly, it is necessary to go beyond the manifested symptom to understand hidden thoughts and ask ourselves, for example, if behind the symptom there lies a masturbatory fantasy or a delirium. Having accepted the premises that an absence of interior images is the basis of every mental illness, in the hypothesis formulated the origin of an obsessive neurosis goes hand in hand with a dynamic scission of indefinite images stemming from the first months of life.